Evaluation of Natural killer activated receptor NKG2D, Inhibitory receptor KIR2DL1 and soluble ligand MICA in Iraqi patients of Acute myeloid leukemia (Journal of Pharmaceutical Negative Results, 2022)
Background: AML is a leukemic disease that related to the rapidly myeloid proliferation progenitor cells are transformed and leadingto stop proliferation and self-renewing. AML have many abilities to evading immune system one of them down expression of NK cellsactivating receptors NKG2D which is elaborate in in cooperation innate and adaptive immunities, and occupations as a “principalswitch” in influential the stimulation of natural killer (NK) cells. NKG2D can binds to a various ligand molecule, which are onlyexpressed at small concentration in usual cells but can be increase by a cellular tension response. And the realizing soluble NKG2Dligands MICA which is express by tumor cells and by binding with NKG2D lead to activated NK cells.Patients and methods: This study consists of 30 new diagnosed patients with AML and 24 out of 30 patients follow up at 14 days aftertreatment, 20 healthy looking persons match age and sex as control group. NKG2D detection by Flowcytometry and soluble MICAdetection by ELISA.Results: The NK cells activation receptor down expression in patients of AML as well as increase releasing of soluble ligand MICA.Conclusion: The NKG2D in patients with AML down expression which may due to increase soluble ligand MICA which lead to maskNKG2D receptors. There was relationship between down expression of NKG2D besides releasing soluble ligand MICA.